"Pro Planting Machine" : Hi-Tech Corporation / Muhd Norashid Hafizzi Rashid...[et.al] - Dzulkifli, Qhairul Izzaidi; Abdullah Shukri, Nur Alia Syafiqa; Mansor, Mohd Fairuz Akmal; Che Rahim, Fadhilah (Faculty of Plantation and Agrotechnology, 2016)
The "Pro Planting Machine" is product made particularly by HI-TECH Corporations and it a new invention which provides best services especially to farmers. Basically, this product was be evaluated through many aspect and there was several improvement have done to make this product look not complicate and effective. Some innovation have done by our company by add water pump and mini hoe to ease the watering and ploughing. With the main objective is to provide a product that can reduce the usage of time, cost and human energy that help increase the efficiency of farming. It also free from pollution because there is no smoke produces during this machine operation. The product is designed suitable use for smallholder farmer and big plantation.